Pembakaran Premixed Minyak Nabati pada Bunsen Burner Type Silinder - La Muhaya, Syamsul Bahri; Wardana, ING.; Widhiyanuriyawan, Denny (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2015)
In the premixed combustion wave propagation combustion occurs is called the flame front. Premixed flame will propagate at the speed of moving towards the reactants unique. If the speed of the reactants is equal to the speed of propagation of fire, the fire (reaction zone) will be stationary. It is necessary to follow up on the influence of equivalence ratio (Ï†) varied with laminar flame speed (SL) in the premixed combustion of vegetable oil (virgin coconut oil, jatropha and cotton seeds). Research using experimental (true experimental research), which is put through direct observation by the equivalence ratio (Ï†), 1.5, 1.6, 1.7 and 1.8 m / l, to determine the causal relationship. Then the results showed a pattern of fire Bunsen burner pure coconut oil with equivalence ratio (Ï†), namely: 2.00, 1.87, 1.78, and 1.66, jatropha oil with equivalence ratio (Ï†) are: 1.73, 1.62, 1:52, and 1:44 and seed oil kapok with equivalence ratio (Ï†) are: 1.76, 1.65, 1:55, and 1:46, the richer the air the flame pattern that looks smaller and smaller until the blow off. This happens because the richer the air causes the fuel has an air excess so that the fuel (fuel) burning diffusion semakain reduced and cause combustion close to the surface of the tip of the nozzle Bunsen burner to high flame formed shorter until there blow off or extinguished.